RESPON RUSIA TERHADAP SANKSI EKONOMI UNI EROPA TAHUN 2014-2015 - Ningtyas Kusuma, Ni Putu Kristin; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT Economic tensions experienced by Russia due to EU sanctions affect trade relations with the EU. The decline in Russia's export capability has resulted in Russia's trade being much lower than the EU. This positions Russia on a negative trade balance that creates imbalances in the dynamics of Russian and EU trade. Assessing the impact of these economic sanctions, encourages Russia to respond to EU economic sanctions in 2014-2015. The results of this research describe Russia's response to EU economic sanctions by using economic power in the form of economic statecraft. Economic statecraft carried out by Russia is a negative sanction in the form of an embargo on agricultural and food products from EU member countries. Keywords: economic sanctions, response, economic statecraft, embagoes